ANALISIS PELAKSANAAN DAN PENGUNGKAPAN TANGGUNGJAWAB SOSIAL PERUSAHAAN PERBANKAN DI INDONESIA (Studi Komparatif Bank Pemerintah dan Bank Swasta) - Janah, Asmaul; Saraswati, Erwin (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study investigates Corporate Social Responsibility implementation and disclosure of Indonesian state banks and private banks to find evidence of differences among them. Corporate Social Responsibility implementation and disclosure are identified based on Global Reporting Initiative (GRI) G3.1 guidelines. The population in this study is 31 Indonesian banks listed in Indonesian Stock Exchange (IDX) in 2011. 20 banks are selcted by using nonprobability random sampling. Research method of this study uses mix method research combining quantitative and qualitative approaches. The differences among state banks and private banks are tested using Mann Whitney U and Paired T Test statistic. The result indicates that there are significant differences in total disclosure of Corporate Social Responsibility and in each of the GRI indicators among the state and private banks. Keyword: Corporate Social Responsibility, Disclosure, Implementation, Private Bank, and State Bank